Electrical activity of the diaphragm during neurally adjusted ventilatory assist in pediatric patients. Issue 9 (7th August 2014) - Kallio, Merja; Peltoniemi, Outi; Anttila, Eija; Jounio, Ulla; Pokka, Tytti; Kontiokari, Tero
Summary Background Neurally adjusted ventilatory assist (NAVA) is a ventilation mode which provides respiratory support proportional to the electrical activity of the diaphragm (Edi). The aims of this trial were to assess the feasibility of aiming at peak Edi between 5 and 15 µV during NAVA in clinical practice, to study the effect of age, sedation level and ventilatory settings on the Edi signal and to give some reference values for Edi in a pediatric population. Methods As a part of a larger randomized controlled trial, 81 patients received Edi catheter for monitoring Edi and guiding NAVA ventilation. The goal for peak Edi during invasive ventilation was 5–15 µV. Edi activity and NAVA levels were observed during invasive ventilation and an hour after extubation. Results Sixty‐six patients with healthy lungs (81.5%) were ventilated, mostly as part of postoperative care, while respiratory distress was the indication for invasive ventilation in the remaining 15 patients (18.5%). NAVA levels varied from 0.2 to 2.0 cmH2O/µV in the patients with healthy lungs, but were higher, from 0.7 to 4.0 cmH2O/µV, in the respiratory distress patients (P < 0.001). The latter had higher peak Edi values in all phases of treatment. The effect of age and level of sedation on Edi was statistically significant, but carried only limited clinical relevance. The peak post‐extubation Edi levels of the patients with healthy lungs and respiratory distress, respectively, were 9 ± 7 and 20 ± 14 µV. Two out of the three patients for whom extubation failed had an atypical Edi pattern prior to extubation. Conclusions Optimizing the level of support during NAVA by aiming at a peak Edi between 5 and 15 µV was an applicable strategy in our pediatric population. Relatively high post‐extubation Edi signal levels were seen in patients recovering from respiratory distress. Information revealed by the Edi signal could be used to find patients with a potential risk of extubation failure. Pediatr Pulmonol. 2015; 50:925–931. © 2014 Wiley Periodicals, Inc.